Induction Versus Noninduction Antiviral Therapy for Chronic Hepatitis C Virus in Patients with Congenital Coagulation Disorders: A Canadian Multicentre Trial. (2007) - Chatterjee, A; Swain, MG; Lee, SS; Bain, VG; Peltekian, K; Croitoru, K; Adams, PC; Kaita, K; Teitel, J; Heathcote, EJ
Abstract : BACKGROUND: Patients with congenital coagulation disorders and chronic hepatitis C virus (HCV) infection have multiple risk factors (ie, infection predominantly with genotype-1 HCV, long duration of the disease, HIV coinfection and male sex) for poor response to antiviral therapy. The present study compared induction therapy with interferon-alpha (IFN-α)-2b with standard IFN-α2b therapy. Pegylated IFN was not available at the time that the study was initiated. PATIENTS AND METHODS: A randomized study was performed comparing the efficacy of traditional IFN-α2b therapy (group A –three million units, three times weekly for 24 to 48 weeks) and daily ribavirin (1.0 g to 1.2 g according to weight for 24 to 48 weeks), with induction IFN-α2b therapy (group B – three million units, daily for eight weeks followed by the same dose administered three times a week for a further 16 to 40 weeks) and daily ribavirin (same dose as above) in IFN-naive patients with congenital coagulation disorders and chronic HCV infection. RESULTS: Between 2000 and 2003, 54 HIV-negative patients were recruited and randomly assigned to group A or B (n=27 each). Both groups were comparable in terms of age, sex, ethnicity, body mass index, baseline HCV RNA titre, viral genotype, liver fibrosis stage and type of coagulation disorder. Induction therapy did not significantly alter sustained virological response rates (group A 50%, group B 50%; P=1.0). Multiple logistic regression analysis indicated that induction therapy did not benefit individuals with difficult-to-treat infection (ie, those infected with genotypes 1 and 4, or those with high baseline viral loads). CONCLUSIONS: There was no benefit with induction antiviral therapy for HCV infection in individuals with congenital coagulation disorders.